O dano moral coletivo como sanção reparadora nos crimes contra a administração pública - Oliveira, Luiz Fernando Silva (2019)
Collective moral damage has been used as a measure to discourage illicit practices against an indeterminate number of victims, and it is time to use it as a remedial sanction in crimes committed against the Public Administration, commonly known as corruption offenses. The improvement of the legal system through the application of collective moral damage as a penalty, in the criminal sentence, starts from a new dogmatic proposal, of defining corruption as a violation of normative expectations, causing frustration of the collective and generating disbelief of the people, Power, in the legal system. The sanction imposed on the individual as a collective moral damage aims to punish him for the conduct that has caused social frustration for non-compliance with the norm and to regain the collective confidence that the norm remains in force and maintain the expectation that it will continue to be fulfilled